2023
DOI: 10.31235/osf.io/b3ezy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generative AI in the Workplace: Employee Perspectives of ChatGPT Benefits and Organizational Policies

Abstract: Research Questions•What attitudes do professionals hold towards the impact of AI on society and their jobs? How do early adopters of ChatGPT differ in their attitudes towards the impact of AI on society and their jobs? •In what ways are professionals using ChatGPT? How do these uses differ by managerial status?•What do professional perceive as benefits of generative AI? How do they differ in these views based on level of ChatGPT adoption and managerial status?•What do professionals perceive as the benefits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 6 publications
0
6
0
2
Order By: Relevance
“…Cependant, d'autres organisations ont déjà intégré ces outils à leurs pratiques et les emploient pour effectuer diverses tâches, comme la création de contenu, la programmation, le service client ou en ressources humaines (Lu, 2023). De plus, de nombreux employés utilisent aussi des outils d'IA générative dans leurs tâches quotidiennes, et plusieurs le font d'ailleurs sans en aviser leurs supérieurs (Cardon et al, 2023). Malgré cet usage répandu, plusieurs entreprises n'ont toujours pas adopté de directives claires concernant l'utilisation de l'IA générative en milieu professionnel (Cardon et al, 2023).…”
Section: La Transparence Et L'encadrementunclassified
See 1 more Smart Citation
“…Cependant, d'autres organisations ont déjà intégré ces outils à leurs pratiques et les emploient pour effectuer diverses tâches, comme la création de contenu, la programmation, le service client ou en ressources humaines (Lu, 2023). De plus, de nombreux employés utilisent aussi des outils d'IA générative dans leurs tâches quotidiennes, et plusieurs le font d'ailleurs sans en aviser leurs supérieurs (Cardon et al, 2023). Malgré cet usage répandu, plusieurs entreprises n'ont toujours pas adopté de directives claires concernant l'utilisation de l'IA générative en milieu professionnel (Cardon et al, 2023).…”
Section: La Transparence Et L'encadrementunclassified
“…De plus, de nombreux employés utilisent aussi des outils d'IA générative dans leurs tâches quotidiennes, et plusieurs le font d'ailleurs sans en aviser leurs supérieurs (Cardon et al, 2023). Malgré cet usage répandu, plusieurs entreprises n'ont toujours pas adopté de directives claires concernant l'utilisation de l'IA générative en milieu professionnel (Cardon et al, 2023). Compte tenu des limites et des failles de ces systèmes, mais aussi des enjeux éthiques et juridiques spécifiques associés à leur utilisation dans différents contextes, il apparaît important que les organisations mettent en place des mesures qui permettent davantage de transparence et un encadrement adéquat de l'IA générative au travail.…”
Section: La Transparence Et L'encadrementunclassified
“…A survey of 621 business leaders in the United States who are early adopters of the technology in February 2023 reported that ChatGPT is being used for writing job descriptions in 77% of companies; drafting interview questions, 66%; responding to job applicants, 65%; copywriting/content creation, 58%; customer support, 57% of companies; summarizing meetings and corporate documents, 52%; research, 45%; and generating task lists, 45% (Williams, 2023). A survey study of working adults in the United States found that roughly 42% were using ChatGPT to research a topic or generate ideas for work, 32% for drafting messages, 26% for drafting reports, and 22% for editing text (Cardon et al, 2023).…”
Section: Generative Ai Adoption and Ai-assisted Writing In The Workplacementioning
confidence: 99%
“…A variety of frameworks of AI literacy exist; however these frameworks primarily focus on the technical aspects of AI use (Ng et al, 2021). One unique aspect of generative AI tools is use in everyday business communication tasks, which are primarily social in nature (Cardon et al, 2023). In their review of work about AI and business communication, Getchell et al (2022) specifically call for scholars to develop frameworks to discuss AI-assisted communication.…”
mentioning
confidence: 99%
“…Features such as captions, real-time translation, meeting transcripts, voice-based commands, and automated note-taking are among features that are available in many online meeting platforms. Speech recognition, natural language processing, image recognition, emotion recognition, and other technologies continue to allow new features in online meetings (Carradini et al, 2023).…”
Section: Introductionmentioning
confidence: 99%